PENGARUH MINAT BELAJAR, DUKUNGAN ORANG TUA, DAN FASILITAS SEKOLAH TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI SISWA SD DEBORA BANJARNEGARA - Bayu Wicaksono, Genta; Qoriah, Anirotul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical education plays an important role in supporting the physical, mental, and social development of elementary school students. However, its implementation still faces several challenges, including low student learning interest, limited parental support, and inadequate school facilities. This study aims to analyze the influence of learning interest, parental support, and school facilities on physical education learning at SD Debora Banjarnegara. This study employed a quantitative approach with an ex post facto design. The population consisted of 46 students using a total sampling technique. Data were collected through questionnaires, observations, and documentation, and analyzed using multiple linear regression with the assistance of JASP software. The results showed that descriptively all variables were in the low category. However, inferential analysis indicated that learning interest, parental support, and school facilities had a positive and significant effect on physical education learning, both partially and simultaneously. Learning interest was found to be the most dominant variable influencing learning outcomes. The coefficient of determination (R² = 0.947) indicates that 94.7% of the variance in physical education learning is explained by these variables. In conclusion, improving students’ learning interest, strengthening parental support, and providing adequate school facilities are essential to enhance the quality of physical education learning.